Analisis Persepsi Vaksinasi Covid-19 dengan Pendekatan Health Belief Model pada Ibu Hamil dan Ibu Nifas di Bali - Ni Komang Tri Agustini; Luh Gde Nita Sri Wahyuningsing (Universitas Malahayati Lampung, 2023)
ABSTRACT Covid-19 still a health problem in the world. One of the efforts made by the government was the Covid-19 vaccination for the society, including pregnant women and nursing mothers. However, in practice there are still many pregnant women and nursing mothers who do not follow the government's recommendation to vaccinate against Covid-19.This study was to identify and analyze perceptions using the Health Belief Model approach (seriousness, vulnerability, benefits, obstacles, and desire to move) of Covid-19 vaccination in pregnant and lactating women in the Province of Bali. The design used in this research is descriptive analytic cross sectional. The research was conducted in July-October 2022 in the Province of Bali. Inclusion criteria for pregnant women and postpartum women in Bali Province aged 18-39 years. The research sample is 270 people. The instrument used was a questionnaire with a reliability test result of 0.8614. Data were analyzed by SPSS with univariate and bivariate tests with Chi Square. Components of the health belief model that have a relationship with knowledge about Covid-19 vaccination are perceived seriousness with p-value = 0.000 (p0.05), perceived vulnerability with p-value = 0.000 (p0.05), perception benefits with p-value = 0.000 (p0.05), perceived barriers with p-value = 0.000 (p0.05), and actions to act with p-value = 0.000 (p0.05). Mothers' perceptions about the seriousness, vulnerability, benefits, barriers and actions taken about the Covid-19 vaccination have a significant relationship with the mother's knowledge about the Covid-19 vaccination. Keywords: Perception, Pregnant And Lactating Women, Covid-19 Vaccination ABSTRAK Covid-19 sampai saat ini masih menjadi masalah kesehatan di dunia. Salah satu upaya yang dilakukan pemerintah adalah vaksinasi Covid-19 bagi masyarakat umum termasuk ibu hamil dan ibu menyusui. Namun pada pelaksanaannya masih banyak ibu hamil dan ibu menyusui yang tidak mengikuti anjuran pemerintah untuk melakukan vaksinasi Covid-19. Penelitian ini untuk mengidentifikasi dan analisis persepsi dengan pendekatan Health Belief Model (keseriusan, kerentanan, manfaat, rintangan, dan keinginan untuk bergerak) vaksinasi Covid-19 pada ibu hamil dan ibu menyusui di Provinsi Bali. Desain yang digunakan dalam penelitian ini adalah deskriptif analitik cross sectional. Penelitian dilakukan bulan Juli-Oktober 2022 di Provinsi Bali. Kriteria inklusi ibu hamil dan ibu nifas di Provinsi Bali usia 18-39 tahun. Sampel penelitian 270 orang. Instrumen yang digunakan kuisioner dengan hasil uji reliabilitas 0,8614. Data dianalisis dengan SPSS dengan uji univariat dan bivariat dengan Chi Square. Komponen health belief model yang memiliki hubungan dengan pengetahuan tentang vaksinasi Covid-19 yaitu persepsi keseriusan dengan p-value = 0,000 (p0,05), persepsi kerentanan dengan p-value = 0,000 (p0,05), persepsi manfaat dengan p-value = 0,000 (p0,05), persepsi hambatan dengan p-value = 0,000 (p0,05), dan tindakan untuk bertindak dengan p-value = 0,000 (p0,05). Persepsi ibu tentang keseriusan, kerentanan, manfaat, hambatan dan tindakan bertindak tentang vaksinasi Covid-19 memiliki hubungan bermakna dengan pengetahuan ibu tentang vaksinasi Covid-19. Kata Kunci: Persepsi, Ibu Hamil Dan Ibu Menyusui, Vaksinasi Covid-19